VERBAL AND VISUAL SIGN IN VALENTINE'S DAY EDITION CHOCOLATE ADVERTISEMENT - I Made Hery Sudiartawan; Ni Wayan Suastini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Every advertised product or service has a meaning contained in it, such as a verbal or visual sign that is inserted. This study wants to explain and explain the verbal meaning and visual signs contained in Valentine's Day Edition chocolate advertisements. The analysis process used by the researcher is a detailed observation method using a qualitative descriptive method. The supporting theory was put forward by Saussure (1983:65) to describe verbal and visual signs, Barthes (1967) to explain the meaning of verbal and visual signs and Wierzbicka (1996) to explain the colors used in Valentine's Day Edition chocolate advertisements. In analyzing this, there were 9 verbal and 15 visual signs from 3 Valentine’s Day Edition chocolate advertisements and 6 connotative and 14 denotative meaning that were found by the researcher. This indicates that the company wants to make the advertised product known to the public with different concepts and ideas by using attractive verbal and visual signs.